Sounds in the desert: New evidence of ambos in Shivta churches - Maayan-Fanar, Emma (Palestine exploration quarterly, 2024)
A hexagonal marble object from the Rockefeller Museum, Jerusalem, found during excavations of H. D. Colt in the 1930s, has been identified as a canopy of an ambo. It probably belonged to one of the churches in Byzantine Shivta and is published here for the first time. Dated most likely to the 6th–early 7th century, it constitutes rare evidence of this liturgical furnishing in the Negev, raising questions concerning its unique iconography and acoustic applications.